Synergistic Effect of the Heterostructure of Au Nanoislands on TiO2 Nanowires for Efficient Ionization in Laser Desorption/Ionization Mass Spectrometry - Kim, Moon-Ju; Yun, Tae Gyeong; Noh, Joo-Yoon; Park, Jong-Min; Kang, Min-Jung; Pyun, Jae-Chul (American Chemical Society, 2019)
A combination nanostructured matrix with metal Au nanoislands and semiconductor TiO2 nanowires is presented to enhance both desorption and ionization efficiency in laser desorption/ionization (LDI) mass spectrometry. The heterostructure of Au nanoislands on TiO2 nanowires was fabricated via (1) TiO2 nanowire synthesis through a modified wet-corrosion method and (2) Au nanoisland formation through thermal annealing of a sputtered Au layer on the TiO2 nanowires. Herein, the synergistic effect of this heterostructure for highly efficient ion production was experimentally elucidated in terms of the formation of high temperature on the surface of Au and the creation of a Schottky barrier at the Au-TiO2 interface. Finally, four types of immunosuppressors were analyzed to demonstrate the improved ionization performance of the heterostructure for LDI mass spectrometry.
Keywords: SURFACE-PLASMON RESONANCE; HYDROTHERMAL TREATMENT; DESORPTION-IONIZATION; GOLD NANOPARTICLES; RECENT PROGRESS; MATRIX; CHIP; NANOMATERIALS; FABRICATION; MOLECULES